Capacity Strategy Planning for Frozen Corndog Business: A Decision Tree and TELOS Framework Approach - Angela Cecilia Saputra (Publikasi Indonesia, 2026)
Capacity planning is a critical challenge for micro, small, and medium enterprises (SMEs), especially in Indonesia, where the frozen food sector is experiencing rapid growth. This study examined Enci Corndog, a micro-sized B2B frozen corndog business in Karawang, Indonesia, which faced a significant capacity gap: current production was 8,736 units per year, while projected demand reached 29,782 units by 2030 under a strong growth scenario, resulting in capacity utilization of 340.91%. Three strategic alternatives were analyzed: (A1) investment in new machines, (A2) outsourcing dough production, and (A3) extending working hours. A mixed-method approach combining Decision Tree financial analysis, including Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR), with TELOS feasibility assessment was applied. The results showed that Alternative 1 provided the highest Expected Value (Rp370,700,493), with an NPV of Rp414,620,498, an IRR of 240.46%, and a BCR of 12.05 under the strong growth scenario, along with the highest TELOS feasibility score (3.15 out of 4.00). The study concluded that investment in new machines was the most feasible and profitable capacity expansion strategy. This alternative increased annual production capacity to 31,200 units through 2030. However, outsourcing and extended working hours remained viable options only as short-term capacity supplement.